Meditation interventions efficiently reduce cortisol levels of at-risk samples: a meta-analysis. Issue 1 (2nd January 2021) - Koncz, Adam; Demetrovics, Zsolt; Takacs, Zsofia K.
ABSTRACT: Previous meta-analytic results showed beneficial effects of meditation interventions for cortisol levels. In the present meta-analysis we tested whether effects are larger for those who might be in need of such stress reduction programs due to a risk for elevated cortisol levels as compared to no-risk samples. We included RCTs that measured change in cortisol levels. Based on 10 studies using blood samples meditation interventions had a significant, medium effect from pre-to post-test compared to the control group. Upon closer inspection, this effect was only present for at-risk samples, that is, patients with a somatic illness. In the 21 studies using saliva samples the effect was small and not significant, but there was a marginally significant effect for groups living in stressful life situations. This pattern may suggest that that meditation interventions are most beneficial for at-risk populations. These interventions might provide people with strategies of stress management that can contribute to well-being. Preliminary results suggest that benefits of meditation interventions might not fade with time.